Movement with meaning: integrating information into meta‐ecology. Issue 8 (2nd March 2022) - Little, Chelsea J.; Rizzuto, Matteo; Luhring, Thomas M.; Monk, Julia D.; Nowicki, Robert J.; Paseka, Rachel E.; Stegen, James C.; Symons, Celia C.; Taub, Frieda B.; Yen, Jian D. L.
Abstract : Fluxes of matter, energy and information over space and time contribute to ecosystems' functioning and stability. The meta‐ecosystem framework addresses the dynamics of ecosystems linked by these fluxes but, to date, has focused solely on energy and matter. Here, we synthesize existing knowledge of information's effects on local and connected ecosystems and demonstrate how new hypotheses emerge from the integration of ecological information into meta‐ecosystem theory. We begin by defining information and reviewing how it flows among ecosystems to affect connectivity, local ecosystem function and meta‐ecosystem dynamics. We focus on the role of semiotic information: that which can reduce an individual's – or a group's – uncertainty about the state of the world. Semiotic information elicits behavioral, developmental and life history responses from organisms, potentially leading to fitness consequences. Organisms' responses to information can ripple through trophic interactions to influence ecosystem processes, their local and regional dynamics, and the spatiotemporal flows of energy and matter, therefore information should affect meta‐ecosystem dynamics such as stability and productivity. While specific subdisciplines of ecology currently consider different types of information (e.g. social and cultural information, natural and artificial light or sound, body condition, genotype and phenotype), many ecological models currently account for neither the spatio–temporal distribution of information nor its perception by organisms. We identify the empirical, theoretical and philosophical challenges in developing a robust information meta‐ecology and offer ways to overcome them. Finally, we present new hypotheses for how accounting for realistic information perception and responses by organisms could impact processes such as home range formation and spatial insurance, and thus our understanding of ecological dynamics across spatial and temporal scales. Accounting for information will be essential to understanding how dynamics such as fitness, organismal movement and trophic interactions influence meta‐ecosystem functioning, and predicting how ecosystem processes are affected by anthropogenic pressures.